Patients with a previous stroke attack who suffer from blood pressure control or regulation in Saudi Arabia - Hassan, Khaled M.; Alqahtani, Abdulwahab A.; Alotaibi, Mohammed W.; Alahmari, Abdulaziz A.; Alanazi, Salwa M.; Al-Hussain, Ghadah O.; Alnahdi, Mesedah A.; Alharbi, Faisal A.; Alshehri, Ahmed A.; Aloraini, Ziyad A.; Almutairi, Sulaiman H.; Baw, Bara A.; et al. (International Journal Of Community Medicine And Public Health, 2020)
This study aims to discuss the blood pressure (BP) control with patients who suffer from a previous stroke or transient ischemic attack (TIA) in Saudi Arabia, to discuss the risk factors and to examine antihypertensive medication-dosing. The most recent office-based BP reading was compared with the BP <140/90 mmHg objective of the National Institute for Health and Care Excellence (NICE) (NG136) and European Society of Hypertension or European Society of Cardiology (ESH/ESC 2013) study participants. By benchmarking prescription doses for each drug with the World Health Organization-defined daily dosing (WHO-DDD) guidelines, optimal anti-hypertensive medication dosing was calculated. In 10 procedures, we found 328 patients with a prior stroke or TIA. When assessed against the ESH/ESC and NICE guidelines (63.1 percent, n=207), blood pressure was controlled in nearly two-thirds of patients. Of those with BP 140/90 (n=116), just under half (n=44, 47.3 percent) were sufficiently dosed relative to the WHO-DDD guidelines in all anti-hypertensive medicines. To conclude, in at least one-third of patients with a prior stroke or TIA, blood pressure regulation remains sub-optimal. Half of these patients were able to respond to an elevation of the anti-hypertensive dose. Further analysis is needed to see how best to control blood pressure in primary care patients with a previous stroke or TIA, since the majority of hypertension consultations take place in this setting.